Comparison between probiotic lozenges and drinks towards periodontal status improvement of orthodontic patients - Natasia Melita Kohar; Victor Emmanuel; Luki Astuti (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2015)
Background: Fixed orthodontic appliances may interfere with daily oral hygiene procedure, causing more abundant plaque accumulation, therefore increasing the risk of periodontal disease. Probiotic methods represent a breakthrough approach in maintaining oral health and preventing periodontal disease. Purpose: The aim of this study was to compare the effect between probiotic lozenges containing Lactobacillus reuteri and probiotic drinks containing Lactobacillus casei strain Shirota towards periodontal status of orthodontic patients. Method: Fixed orthodontic patients (n=30) from Faculty of Dentistry, Trisakti University Dental Hospital were included in this clinical trial. Periodontal status consisting of Plaque Index (PlI), Interdental Hygiene Index (HYG), and Papillary Bleeding Index (PBI) were then recorded from each patient. All patients received the phase one of periodontal treatment, as well as plaque control instruction. The subjects (n=10/gp) were randomly assigned to one of three groups; control group; probiotic lozenges group (Biogaia®); and probiotic drinks group (Yakult®). For 14 days, the probiotic groups were instructed to use the probiotic. Periodontal index improvement (PlI, HYG, and PBI) was found in all groups after 14 days research periode. These indices were then analyzed using Kruskal-Wallis analysis test. Result: It was found that L. reuteri and L. casei strain Shirota may improve periodontal status in fixed orthodontic patients. The best results were obtained from probiotic lozenges group. However, the results were not statistically significant (p>0.05). Conclusion: It was concluded that probiotics consumption containing L. reuteri and L. casei strain Shirota may slightly improve periodontal status in fixed orthodontic patients.